The Implementation of Customer Engagement Strategies through Social Media in SMEs - Arifin Djakasaputra; Hergian Stephanie; Mikael Satriohantoro (International Journal of Social Science and Community Service, 2025)
Customer engagement strategy emphasizes marketing activities to build good relationships with customers, with the aim of increasing customer loyalty, satisfaction, and retention. customer engagement can be improved through social media. The activity partner is engaged in the business of making songket cloth, as well as cracker snacks, located in Jambi. This activity aims to assist partners in increasing knowledge about customer engagement through social media. The activity method is carried out with training related to understanding customer engagement, social media, how partners relate to customers online, how partners can build good relationships with customers so that later it will have an impact on increasing sales. This strategy also helps partners increase customer loyalty and open a wider market for the business being carried out, training is carried out online using the zoom application. Through this activity, it is hoped that it can increase partners' knowledge in building long-term relationships with customers. The output of the activity is in the form of publications to journals and HKI (Intellectual Property Rights).